Modelling Local Food Depletion Effects in Mussel Rafts of Galician Rias - Duarte, Pedro (2008)
Mollusc culture is one of the most important types of mariculture, with suspension feeding bivalves being among the most cultivated organisms. In the last years, there has been a growing concern about carrying capacity (CC) of natural ecosystems for bivalve culture, because of decreases in growth rates and mass mortalities due to overstocking. Several methods have been proposed for CC estimation. The simplest are based on average properties integrated over various time scales, like water renewal rate, phytoplankton primary production and bivalve clearance rate. If the time scale of the former two processes is larger than the time scale for bivalve filtration than, bivalve standing stock is over ecosystem CC. More complex approaches are based on ecosystem box modelling or coupled physical-biogeochemical models. The objective of this work is to evaluate production CC for mussel rafts in Galician Rias as a function of mussel loads and current velocities. For this purpose an analytical model was developed and used to find conditions that maximize raft production. Obtained results suggest that CC at the raft scale has not been exceeded by current culture practices. However, it does not seem advisable to increase mussel loads per raft. Therefore, any possible increase in mussel production should be considered at a higher spatial scale.